KATE THEIMER, ed., A Different Kind of Web: New Connections Between Archives and Our Users - Harvey, Kathryn (Archivaria, 2012)
A Different Kind of Web: New Connections Between Archives and Our Users. KATE THEIMER, ed. Chicago: Society of American Archivists, 2011. xvii, 369 p. ISBN 1-931666-39-3.